Snow Lotus : Exploring the Eternal Moment - Leschak, Peter M., 1951- (Book collections on Project MUSE., 1996)
A Native American proverb states that "yesterday is ashes, tomorrow is wood, only today does the fire burn brightly." This series of essays, set in the north woods of Minnesota, is woven around the theme of the importance of being alive and aware in the present. Deeply rooted in the natural world, The Snow Lotus shares the philosophical and emotional insights author Peter M. Leschak has acquired from a life lived close to nature.